The Perception of Sunway University Students on Green Products: A Case Study on Students of Department of Communication and Liberal Arts - Ramlie, Azman; Ting, Jacqueline Zi Yee (Universiti Sains Malaysia, 2016)
Since the year of 2000, green products has started to become a trend in the marketplace where increasing numbers of manufacturers has begin to use green attributes to associate with their products. This research is beneficial to companies are creating green products that are targeted towards students as their main target market. This research will help manufacturers to understand the perceptions of students toward green products and can later help them to improvise their products to meet the student demands and preference on green products. The purpose of this study is to understand Sunway University students’ perception towards green products. Researcher examined four types of perceptions which are perceived value, perceived risk, perceived price, and perceived quality. Survey questionnaire was distributed to Department of Communication & Liberal Arts students. The data analysis was based on 150 respondents. The findings reveal that perceived value plays the main role in the students’ perceptions on green products followed by, perceived value, perceived risk and perceived quality